Compact non-invasive millimeter-wave glucose sensor - Siegel, Peter H.; Tang, Adrian; Virbila, Gabriel; Yanghyo Kim; Chang, M. C. Frank; Pikov, Victor (International Conference on Infrared, Millimeter, and Terahertz Waves (Print), 2015)
The authors describe a compact non-invasive CMOS-circuit-based glucose monitor using millimeter-wave transmission for use on animal and human subjects. Using an earlier device, in vivo measurements were performed through the ear in anesthetized animals and correlated with blood glucose concentration from test strips. In addition, millimeter wave absorption through glucose-containing solutions was measured in specialized liquid transmission cells and is shown to correlate with the animal and separate in vitro data. Design and performance information on the CMOS transceiver are given.